Development of The Star Patch Wearable antenna for ISM Band Application - Faisal Ramadhan; Rudy Yuwono; Fauziahanim Binti Che Seman (Jurnal Mahasiswa TEUB, 2016)
This paper proposes a prototype of wearableantenna by using a star patch design. The research objective ismainly to observe some of the characteristic of the wearableantenna that is bending on the curvy structure. During the initialstudy, an intensive literature has been conducted to investigate theeffects of the substrate material, and some of the design ofwearable antenna. The designs and simulations in this study aredone using the Computer Simulation Technology (CST)Microwave Studio software. Time domain solver in CST is used tosimulate the designs of the wearable antenna. This antenna is usingthe polyimide film as the substrate with dielectric permittivity(???????? = ????. ????). The polyimide film has a better performance in termsof flexibility, low loss tangent, dielectric constant, and highstability for the wearable application. The antenna performancehas been measured such as (????????????), impedance bandwidth, radiationpattern, and gain. This antenna provides a minimum resonantfrequency at 2.45 GHz which is the (????????????) is -27.67 dB in the flatcondition. The impedance bandwidth of the star patch antenna isrelatively large, which is 610 MHz it could overcome the shiftedresonant frequency caused by the bending effect. From the study,it is found that the star patch antenna offers the best performancein terms of return loss, bandwidth, radiation pattern, and gain.Star patch antenna is also less affected by the effects caused bybending the antenna. Comparisons between the simulated andmeasured results for proposed antenna will be discussed in thispaper.Keywords— Wearable Antenna, Star Patch design, ISM Band,WBAN